Curcumin’s Antioxidant Properties in Stable Coronary Artery Disease Patients Undergoing Percutaneous Coronary Intervention: A Randomized Controlled Trial - Todung Silalahi; Idrus Alwi; Frans Suyatna; Katarina Dewi Sartika; Christopher Surya Suwita (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Percutaneous coronary intervention (PCI) is the most common intervention for coronary artery disease (CAD) with very low complications. High oxidative stress post-PCI is associated with further atherosclerosis progression. Curcumin, extracted from a specific type of herbs, exhibits anti-oxidant properties by acting as hydrogen and electron donor for superoxide radicals. The aim of this study is to determine the effect of curcumin’s antioxidant properties in reducing oxidative stress of post-PCI in stable CAD.METHODS: This study was a double-blind parallel randomized controlled trial among 50 stable CAD patients undergoing PCI in Cipto Mangunkusumo General Hospital and Jakarta Heart Center. The subjects received either 45 mg/day curcumin or placebo 7 days pre-PCI until 48 hours post-PCI. Reduced oxidative stress markers (decreased MDA or increased GSH) were measured in 3 phases (7 days pre-PCI, 24 hours post-PCI, 48 hours post-PCI).RESULTS: Curcumin group showed increased MDA from baseline to 24 hours (Δ1=0.01 vs. 0.03; p=0.3) and decreased MDA from baseline to 48 hours (Δ2=-0.06 vs. 0.03; p=0.9). While, curcumin group showed decreased GSH from baseline to 24 hours (Δ1=-49.7% vs. 12.2%; p=0.4) and from baseline to 48 hours (Δ2=-19.09% vs. 11.4%; p=0.6). However, no significant changes were found in malondialdehide (MDA) and glutathione (GSH) level after the intervention.CONCLUSION: The 45 mg/day curcumin supplementation from 7 days pre-PCI until 48 hours post-PCI had no significant antioxidant effect in stable CAD post-PCI.KEYWORDS: coronary artery disease, curcumin, antioxidant, percutaneous coronary intervention